Axonal Cleaved Caspase-3 Regulates Axon Targeting and Morphogenesis in the Developing Auditory Brainstem - Rotschafer, Sarah E.; Allen-Sharpley, Michelle R.; Cramer, Karina S. (Frontiers in Neural Circuits, 2016)
Caspase-3 is a cysteine protease that is most commonly associated with cell death. Recent studies have shown additional roles in mediating cell differentiation, cell proliferation, and development of cell morphology. We investigated the role of caspase-3 in the development of chick auditory brainstem nuclei during embryogenesis. Immunofluorescence from embryonic days E6-13 revealed that the temporal expression of cleaved caspase-3 follows the ascending anatomical pathway. Expression is first seen in the auditory portion of VIIIth nerve including central axonal regions projecting to nucleus magnocellularis (NM), then later in NM axons projecting to nucleus laminaris (NL), and subsequently in NL dendrites. To examine the function of cleaved caspase-3 in chick auditory brainstem development, we blocked caspase-3 cleavage in developing chick embryos with the caspase-3 inhibitor Z-DEVD-FMK from E6 to E9, then examined NM and NL morphology and NM axonal targeting on E10. NL lamination in treated embryos was disorganized and the neuropil around NL contained a significant number of glial cells normally excluded from this region. Additionally, NM axons projected into inappropriate portions of NL in Z-DEVD-FMK treated embyros. We found that the presence of misrouted axons was associated with more severe NL disorganization. The effects of axonal caspase-3 inhibition on both NL morphogenesis and NM axon targeting suggest that these developmental processes are coordinated, likely through communication between axons and their targets.